2002
DOI: 10.1002/kin.10026
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of solid‐state reactions toward consensus, Part 3. Searching for consistent kinetic results: SCTA vs. conventional thermal analysis

Abstract: This paper is the third part of a review of some of the controversial kinetic aspects of conventional thermal methods. We open a discussion about the necessity of developing new possibilities and techniques in the field of solid-state reactions. In the last decade we have seen the commercialization of new instruments and apparatus by a number of manufacturers, which allows for carrying out more meaningful experiments. The Sample Controlled Thermal Analysis describes a family of new techniques such as Controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…1). [67][68][69] By plotting f(a) versus time-of-reaction, a linear relation shall be obtained, with the corresponding slope giving the reaction rate of the process.…”
Section: Determination Of Kinetic Parametersmentioning
confidence: 99%
“…1). [67][68][69] By plotting f(a) versus time-of-reaction, a linear relation shall be obtained, with the corresponding slope giving the reaction rate of the process.…”
Section: Determination Of Kinetic Parametersmentioning
confidence: 99%
“…Because the partial pressure of the gases is proportional to the rate, the reaction proceeds at a constant overall rate previously selected by the user, under a constant partial pressure of evolved gas. Previous works have demonstrated the efficiency of CRTA to control the influence of experimental factors [18][19][20]. This method has been previously used to control the texture and the structure for many materials [21][22][23] through kinetic control of the thermal reaction of their precursors, and it has been reported that CRTA has higher sensitivity and resolution than the conventional methods.…”
Section: Introductionmentioning
confidence: 98%
“…The experimental technique of controlled rate thermal analysis (CRTA), which has higher sensitivity and resolution than the conventional thermoanalytical methods, was employed. The CRTA technique has been specially developed to reduce pressure and temperature gradients throughout the sample and to carry out more meaningful experiments 23,24 …”
Section: Introductionmentioning
confidence: 99%